The Relationship Of Knowledge Of Young Girl With A Level Anxiety Toward Sex Signs The Emergency Of Primary (Menarche) (A Study On Student Of Class VII SMPN 3 Bojonegoro) - Isnanda Putri, Evita Muslima (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Teenage was the period of transition from child to adult. Young girl who step on puberty changes the sign of the primary sex (Menarche). Primary sex signs (Menarche) was one of the causes of anxiety of young girl. The purpose of the research was knowed the relationship of knowledge young girl with a level of anxiety toward sex signs the emergence of primary (menarche) in Class VII in SMPN 3 Bojonegoro.Research used corelasional design, approach cross sectional population 148 respondents. Number of samples 60 respondents. Sampling techniques used simple random sampling. Independent variables namely knowledge of primary sex signs (menarche) and the dependent variable i.e. the level of anxiety. Method of data collection with the editing, coding, scoring, tabulating and univariate analysis which continued test spearmen rho.Research results more from most respondents have enough knowledge of as many as 32 (53.3%) and over most of respondents experiencing anxiety as many as 39 (65%). The significance level of the test statistics 1.00 means greater than 0.05 Î± so that there is no relationship of knowledge young girl with a level of anxiety toward sex signs primary (menarche).Knowledge does not affect anxiety because there is another factor that is experience, cognitive changes and emotional conflict. In this case the respondent is expected following the extension, get the support of parents, as well as enable it about UKS programme to resolve the issues facing young girl against level anxiety of primary sex signs (Menarche).